'Life-Stage Dissolution', Infantilization and Antisocial Consumption: Implications for De-responsibilization, Denial and Environmental Harm. (August 2015) - Brisman, Avi; South, Nigel
Hayward (2012, 2013) asserts that the opposition between adolescence and adulthood is increasingly challenged as late-modern capitalist culture artificially extends the former. Hayward introduces the concept of 'life-stage dissolution'—and its attendant bidirectional processes of 'adultification' and 'infantilization'—to propose that it isbecomingdifficult for young people to differentiate and disassociate themselves from the generation immediately ahead of them and vice versa. This article makes a contribution to a 'green cultural criminology' (Brisman and South, 2013b, 2014) by extending Hayward's argument to the realm of environmental harms and concerns. It provides examples of ways in which 'life-stage dissolution' and the resulting 'generational mulch' impede efforts towards environmental protection that might take into account future generations, and it explores how such responsibility is denied even while scientific awareness grows that over-consumption is damaging the environment that future generations will inherit.